Study on Effect of Diatomaceous Earth (DAE) on Afl atoxin-Induced DNA Damage in Visceral and Lymphoid Organs in Broiler Chicken - AW Lakkawar; MI Satyanarayana; HD Narayanaswamy (International Journal of Veterinary Science and Research - Peertechz Publications, 2017)
Background: Limited information exists concerning on the effect of diatomaceous earth (DAE) on aflatoxin-induced DNA damage in visceral and lymphoid organs. Objectives: The present investigation is an attempt to detect the effect ability of Diatomaceous earth (DAE) in reducing the detrimental effects of aflatoxin (AF) in broiler diet was evaluated based on structural characteristic of DNA in liver, kidneys, heart, pancreas, thymus, spleen and bursa of Fabricius. Materials and Methods: Three hundred and sixty healthy unsexed one day old broiler chicks were assigned to 9 groups comprising of control and treatment groups. DAE was supplemented @ 400 and 800 mg Kg-1 of feed along with 0.5 and 1 ppm of AF Kg-1 of feed for a period of 35 days. DNA fragmentation assay was conducted to detect changes in DNA. Results: The DNA fragmentation in the toxin fed birds was severe in liver and lymphoid organs (thymus, spleen and bursa of Fabricius), followed by kidneys, heart and pancreas. The damage was more pronounced at 1 ppm in comparison to 0.5 ppm of dietary afl atoxin. The damage to DNA in most of the organs was reduced in birds of co-treatment groups fed with varying dosage of afl atoxin and DAE in the diet. Conclusions: The present study showed that aflatoxin at graded doses induced marked DNA fragmentation indicating the genotoxic effect of aflatoxins. Addition of diatomaceous earth to aflatoxin mixed feed caused decreased DNA fragmentation in visceral and lymphoid organs.